2006
DOI: 10.1029/2005jd006595
|View full text |Cite
|
Sign up to set email alerts
|

Continuous estimation of winter carbon dioxide efflux from the snow surface in a deciduous broadleaf forest

Abstract: [1] The objective of our study was to estimate CO 2 efflux from the snow surface in a deciduous broadleaf forest throughout the duration of winter on the basis of a continuous measurement of CO 2 concentration at the soil-snow interfaces. Continuous CO 2 efflux was estimated from the CO 2 concentration gradient across the snow cover. We examined the accuracy of the values obtained from the CO 2 concentration gradient across the snow cover by comparing them with the values observed by the closed static chambers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 41 publications
(60 reference statements)
2
22
2
1
Order By: Relevance
“…Our study showed that soil CO 2 effluxes from frozen soils were relatively stable in two forest ecosystems during winter. This result is consistent with many other studies conducted in forest ecosystems (Suzuki et al 2006;Wang et al 2010).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Our study showed that soil CO 2 effluxes from frozen soils were relatively stable in two forest ecosystems during winter. This result is consistent with many other studies conducted in forest ecosystems (Suzuki et al 2006;Wang et al 2010).…”
Section: Discussionsupporting
confidence: 83%
“…Our measured values of mean winter soil CO 2 efflux were higher than all of the values reported for boreal coniferous forest ecosystems or temperate deciduous broad-leaved or hardwood forest ecosystems (Rustad and Fernandez 1998;Kurganova et al 2003;Hubbard et al 2005;Groffman et al 2006;Suzuki et al 2006;Schindlbacher et al 2007;Wang et al 2010). For example, moderate soil CO 2 effluxes of 0.5-0.7 lmol m -2 s -1 were recorded during winter in coniferous forests in Austria, Germany, Russia and USA (Sommerfeld et al 1996;McDowell et al 2000;Kurganova et al 2003;Schindlbacher et al 2007;Muhr et al 2009).…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations